2019
DOI: 10.4162/nrp.2019.13.3.214
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on changes in body composition and fat percentage during the first year of cancer treatment in children

Abstract: BACKGROUNDS/OBJECTIVES Cancer treatment may lead to significant body composition changes and affect growth and disease outcomes in pediatric cancer patients. This prospective study aimed to evaluate short- and long-term body compositions changes focused on body fat during the first year of cancer treatment in children. SUBJECTS/METHODS A prospective study was conducted in 30 pediatric cancer patients (19 hematologic malignancies and 11 solid tumors) and 30 age- and sex-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…Lower lean muscle mass with corresponding accumulation of FM, particularly around the trunk and abdomen, has been observed in children undergoing treatment for paediatric malignancies19 with differences in body composition persisting into young adulthood 20 21. A similar pattern is also observed in young adult survivors of preterm birth 22.…”
Section: Clinical Application Of Body Composition Measurementsmentioning
confidence: 71%
“…Lower lean muscle mass with corresponding accumulation of FM, particularly around the trunk and abdomen, has been observed in children undergoing treatment for paediatric malignancies19 with differences in body composition persisting into young adulthood 20 21. A similar pattern is also observed in young adult survivors of preterm birth 22.…”
Section: Clinical Application Of Body Composition Measurementsmentioning
confidence: 71%
“…However, in children with cancer, muscle mass changes occur independently of changes in bone mineral content, fat mass, and total body mass, suggesting that muscle can and should be considered explicitly and independently from body mass index or adiposity. Yang and Choi 74 illustrated this in a propsective study for longtitudinal assessment of nutritonal status and body composition in newly diagnosed heamatologic malignancy (n = 19) and solid tumor (n = 11) patients. Among 30 children (mean age: 10.9 ± 3.8 years, 70% male), DXA showed that median fat-free mass significantly decreased from 27.4 kg (range, 11.5-53.5 kg) to 26.9 kg (14.4-50.6 kg, p = 0.008) during the first month of cancer treatment, occurring in the absence of total body mass change.…”
Section: Acute Outcomesmentioning
confidence: 97%
“…88 Children with cancer do not seem to return to pretreatment muscle mass amounts, nor recover to the amount of muscle mass of their healthy peers. 74,96 Given limited access to skeletal muscle tissue in children, there is a need for future research to incorporate molecular imaging techniques and animal modeling methods to begin to answer these important mechanistic questions.…”
Section: Radiotherapymentioning
confidence: 99%
“…However, out of the 13 children, 3 did have normal muscle mass at the subsequent assessment, 1 had similarly low muscle mass and we did not have data from the other 9. Existing literature reinforces that during the course of cancer therapy body composition can change considerably [8,9,24,25]. Therefore, longitudinal data would be advantageous to decide whether it is safe to rely on NRS-PC without bio-impedance measures.…”
Section: Developing a Screening Algorithm For The Nutritional Status Of Pediatric Oncology Patientsmentioning
confidence: 99%